2007
DOI: 10.1063/1.2787890
|View full text |Cite
|
Sign up to set email alerts
|

Charge carrier mobility of mixed-layer organic light-emitting diodes

Abstract: The authors report the investigation of the charge transport behaviors in mixed thin films of N , NЈ-diphenyl-N , NЈ-bis͑1-napthyl͒-1,1Ј-biphenyl-4 , 4Ј-diamine and tris͑8-hydroxyquinoline͒ aluminum. The extracted electron and hole drift mobility were found to be sensitive to the compositional fraction and interpreted by energy levels, charge mobilities of neat compounds, and microscopic networks within the mixed systems. The carrier conduction characteristics, therefore, were used to illustrate the electrical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
44
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 19 publications
(16 reference statements)
5
44
0
Order By: Relevance
“…To confirm the relation between MEL and blending ratio, Fig. 1(c [21]. The ratio of 30% agrees well with the ratio in the present experiments in which MEL reaches its maximum.…”
supporting
confidence: 75%
“…To confirm the relation between MEL and blending ratio, Fig. 1(c [21]. The ratio of 30% agrees well with the ratio in the present experiments in which MEL reaches its maximum.…”
supporting
confidence: 75%
“…Here, devices A and B were realized using two different hole transporting host materials having different charge carriers transport abilities, particularly the hole mobility. α-NPB has an ambipolar transporting ability with the hole mobility faster than that of m-MTDATA (S. W. Liu et al, 2007). Thus, mobilities of hole carriers in these mixed host single layer systems rather than hole injection barrier at the ITO/mixed host interface seems to be crucial in deciding the driving voltage.…”
Section: Wwwintechopencommentioning
confidence: 99%
“…The interesting and intriguing results on J-V in mixed host single layer devices may be explained on the basis of existing knowledge on carrier mobilities in organic materials. α-NPB exhibits an ambipolar transporting ability with electron and hole mobility values of 9×10 -4 and 6×10 -4 cm 2 /Vs, respectively (S. W. Liu et al, 2007), while the hole mobility value in m-MTDATA www.intechopen.com is 3×10 -5 cm 2 /Vs. Earlier, it was shown that the charge transport behaviors in mixed thin films of -NPB and Alq 3 are sensitive to (i) compositional fraction, and (ii) charge carriers mobilities of neat compounds (S. W. Liu et al, 2007).…”
Section: Wwwintechopencommentioning
confidence: 99%
See 2 more Smart Citations